The relationship between characteristics of root morphology and grain filling in wheat under drought stress - Xinyu Chen; Yu Zhu; Yuan Ding; Rumo Pan; Wenyuan Shen; Xurun Yu; Fei Xiong (PeerJ, 2021)
Drought is a common yield limiting factor in wheat production and has become a significant threat to global food security. Root system is the organ responsible for water uptake from soil and root growth is closely associated with yield and quality of wheat. However, the relationship between morphological and structural characteristics of root growth and caryopsis enrichment in wheat under drought stress is unclear. In this study, two wheat cultivars (YM13 and YN19) were treated with drought from flowering to caryopsis maturity stage. The changes in morphological structure of roots and characteristics of endosperm enrichment were investigated. Drought stress significantly reduced the root length, plant height, root dry weight and aboveground parts dry weight, whereas the root-shoot ratio of YM13 and YN19 increased by 17.65% and 8.33% under drought stress, respectively. The spike length, spike weight, grains number per spike and 1,000-grains weight of mature wheat also significantly declined under drought stress. Meanwhile, the cross section structure of roots was changed with the enlargement of vascular cylinder and dense distribution of xylem vessels under drought stress. Additionally, drought stress affected the substance enrichment in wheat caryopses, decreasing starch accumulation and increasing protein accumulation of endosperm. Correlation analysis suggested that the root length was closely correlated with the relative areas of amyloplast (0.51) and protein body (0.70), and drought stress increased the correlation coefficient (0.79 and 0.78, respectively). While the root dry weight had a significantly positive correlation with the plant height and aboveground parts dry weight. The results can provide theoretical basis for root architecture optimization, water-saving and high-yield cultivation and quality improvement in wheat.